COVID-19 outbreak management in Western Sydney residential aged care homes: A mixed-methods Donabedian evaluation. - Vincent V Vicencio; Catherine Viengkham; Nicholas Grange; Sophie Norton; Ramon Z Shaban (PLoS ONE)
Outbreaks of the novel respiratory viral disease, SARS-CoV-2 (COVID-19), have caused disproportionate morbidity and mortality for older people living in residential aged care homes. Between June 2021 and December 2022, the Delta and Omicron variants of COVID-19 were responsible for widespread outbreaks in homes across Western Sydney, New South Wales, Australia. To manage outbreaks in affected homes, a targeted response strategy was prepared and deployed in the form of outbreak management teams. This study utilised the Donabedian framework and a two-phase mixed methods design to evaluate the structures, processes and outcomes of the outbreak management teams at the level of the local health district. Phase 1 involved the descriptive analysis of outbreak data from Western Sydney aged care homes, created between June 2021 and December 2022. Phase 2 involved the completion of in-depth semi-structured interviews with 35 participants to explore the outbreak management team response from the perspective of its members and staff from residential aged care homes. Between June 2021 and December 2022, there were 281 outbreaks, 4113 resident cases, 346 hospitalisations and 127 deaths in residential aged care homes across Western Sydney. Structural factors that facilitated the outbreak management response and improved outcomes included smaller home sizes, the absence of shared rooms and bathrooms, adequate staffing and resources, suitable infrastructure, and the integration of the response with wider public health systems. Process facilitators included multi-disciplinary team membership, open communication channels, structured and streamlined procedures and roles, onsite infection control support and education, and long-term capability building. The lessons drawn from participants' experiences aim to improve the outcomes and sustainability of current and future outbreak management strategies.